2018
DOI: 10.3390/molecules23050993
|View full text |Cite
|
Sign up to set email alerts
|

Assessing the Effects of Alloxydim Phototransformation Products by QSAR Models and a Phytotoxicity Study

Abstract: Once applied, an herbicide first makes contact with leaves and soil. It is known that photolysis can be one of the most important processes of dissipation of herbicides in the field. However, degradation does not guarantee detoxification and can give rise to byproducts that could be more toxic and/or persistent than the active substance. In this work, the photodegradation of alloxydim herbicide in soil and leaf cuticle surrogates was studied and a detailed study on the phytotoxicity of the main byproduct on su… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8
1
1

Relationship

2
8

Authors

Journals

citations
Cited by 13 publications
(8 citation statements)
references
References 38 publications
(44 reference statements)
0
8
0
Order By: Relevance
“…The 2D-QSAR model analysis method uses the physicochemical parameters or structural parameter variables related to the compound to study the relationship between chemical substances and biological activity/toxicity by mathematical statistics; this method explains the changes in the physical and chemical properties of the compound caused by structural changes and how the biological activity of the compound is altered by these changes [26,27]. In this study, the genetic toxicity data (pLOEC) of FQs were selected as the dependent variable, and the geometric parameters, electronic parameters, physical and chemical parameters, and spectral parameters of FQs calculated using Gaussian 2009 software and Chemdraw12.0 software were used as the independent variables.…”
Section: Methodsmentioning
confidence: 99%
“…The 2D-QSAR model analysis method uses the physicochemical parameters or structural parameter variables related to the compound to study the relationship between chemical substances and biological activity/toxicity by mathematical statistics; this method explains the changes in the physical and chemical properties of the compound caused by structural changes and how the biological activity of the compound is altered by these changes [26,27]. In this study, the genetic toxicity data (pLOEC) of FQs were selected as the dependent variable, and the geometric parameters, electronic parameters, physical and chemical parameters, and spectral parameters of FQs calculated using Gaussian 2009 software and Chemdraw12.0 software were used as the independent variables.…”
Section: Methodsmentioning
confidence: 99%
“…Kandel et al [63] reported that applying different post-emergence herbicides resulted in higher phytotoxicity at different soybean growth stages than non-treated control. Villaverde et al [54] studied the phytotoxicity of alloxydim herbicide and reported high sensitivity of tomato to this herbicide and its major byproduct. Mehdizadeh et al [42] reported that root and shoot biomass of oilseed rape (Brassica napus L.) was severely affected by metribuzin residues in soil.…”
Section: Herbicides Phytotoxicity and Non-target Organismsmentioning
confidence: 99%
“…The study of metabolic pathways is crucial to the analysis of the biodegradation potential of microorganisms. Sometimes, the intermediate metabolite is more toxic than the parent compound [61][62][63]. These intermediates are ephemeral, in low concentrations, and are readily converted to smaller molecular compounds by oxidation and hydrolysis [64][65][66].…”
Section: N-ethylacetamidementioning
confidence: 99%